Attitudes of Saudi mothers towards prolonged non-nutritive sucking habits in children - Al Johara A. Al-Hussyeen (Elsevier, 2010)
Objectives: The purpose of the present study was to evaluate Saudi mothers' attitude towards non-nutritive sucking habits by their children and report the methods they used to stop these habits. Methods: Across-sectional study involved 181 mothers of preschool children currently engaged in non-nutritive sucking habits (digit and pacifier) were studied. The information was obtained from a self-administered questionnaire completed by the mothers. Results: The majority of mothers (69.1%) were from high socio-economic families, (77%) had university or higher education and more than half of them (58.6%) were employed. About 75% of the children were pacifier users, and 25% of them habitually sucked their digits. Nearly half of the mothers (43.5%) thought that the reason of acquiring the habit was because their children cried a lot at night. The majority of studied mothers (88.7%) considered sucking a harmful habit to their children' teeth, and 69.1% never accepted the sucking habit. High percentage (80.8%) of mothers tried to intervene with these habits and 61.0% of them tried their intervention when children were one year old or less. Most proposed reasons for mothers' intervention with sucking habits were their concerns that the habit might continue until the child become older (53.3%) followed by their concern that the habit might affect their children's permanent teeth (45.3%). The methods used by mothers were mostly non-invasive procedures which included restricting the use of pacifier to specific times in the day (63.0%), followed by reinforcement of positive behaviors and using rewards (26.0%). None of the mothers sought advice from pediatrician while only one mother (0.6%) consulted a dentist about sucking habits. Conclusion: This study shows that Saudi mothers are concerned about sucking habits and recognized the harmful effect on their children. These mothers, however, are in great need for education about ways of preventing the habits in the first place as well as professional advice and help in treatment cessation of already established habits. Keywords: Attitudes, Non-nutritive sucking habits